Vitamin D status among pregnant women of North Macedonia: assessing deficiency rates and associated risks factors: Vitamin D deficiency among pregnant women of N. Macedonia - Atanasova Boshku, Aleksandra (Journal of Medical Biochemistry, 2025)
Objective. Vitamin D is an essential vitamin that plays a key role in maintaining overall health. During pregnancy, the demand for vitamin D increases to support the growing needs of the fetus. Vitamin D deficiency is highly prevalent in pregnant women worldwide. The aim of our study was to evaluate the vitamin D deficiency rate among pregnant women in the Republic of North Macedonia, along with influencing factors. Materials and Methods: We conducted a prospective study of randomly selected pregnant women with different body mass index and in two different seasons among vitamin supplementation users and non-users. Results: A total of 309 pregnant women aged > 18 years were recruited from August 2022 to January 2023, with an average vitamin D concentration of 38.9 (36.6-40.2) nmol/l. During the winter period, 80.8 % of pregnant women had vitamin D deficiency. Conclusion: Despite the fact that more than 77.3 % of pregnant women consume multivitamins containing vitamin D, vitamin D deficiency is highly prevalent among pregnant women especially among obese pregnant woman and during the winter months.